Twórcza orientacja życiowa w sytuacjach kryzysowych - Cudowska, Agata (Kultura-Społeczeństwo-Edukacja, 2022)
The narrative of the article revolves around the belief that creative life orientations are very important in coping with crisis situations. The concept of crisis, its etymology and ways of presenting it in social sciences were shown. Psychological approaches to this category were highlighted as particularly important in counseling and social work. Basic styles of coping with stress, which is an inseparable element of crisis events, were characterized. The essence of the author’s concept of creative life orientation and the features of people preferring this type of orientation, which resulted from theoretical assumptions, and the results of twenty years of research on this category, were presented. The importance of creative preferences in overcoming stress, coping with crisis and achieving well-being were demonstrated.